Investigation of the effıciency of pomegranate (punica granatum l.) peel extract on herpes simplex virus-1 - Irmak Dik; Hatice Pelin Aslım (Eurasian Journal of Veterinary Sciences)
Aim: This study, it was aimed to determine the antiviral activity of pomegranate peel (Punica granatum L.) extract on HSV-1 in vitro. Materials and Methods: Before evaluating the antiviral efficacy, the cytotoxic activity of different concentrations of pomegranate peel extract diluted with distilled water in Vero cell culture was determined. It was determined that this cell culture did not cause cytotoxicity at concentrations lower than 0.87 mg/ mL. Antiviral efficacy was determined by cytopathogenic effect (CPE) after the MTT test and microscopic analysis. Results: It was determined that pomegranate peel extract had significant antiviral activity against HSV-1 at concentrations between 0.87 mg/mL and 0.87x2-5mg/mL. This effect may have been achieved by preventing the virus from entering the cell. Conclusion: It was thought that pomegranate peel extract has antiviral activity against HSV-1 in vitro, and in line with the results obtained, in vivo trials are needed to determine the antiviral activity of Punica granatum L. extract in more detail. In addition, a precise determination of the effectiveness of Punica granatum L. Extract against Herpes viruses and other viruses will contribute to antiviral drug trials in the future.